Vertebral Bone Marrow Heterogeneity Using Texture Analysis of Chemical Shift Encoding-Based MRI: Variations in Age, Sex, and Anatomical Location - Dieckmeyer, Michael; Junker, Daniela; Ruschke, Stefan; Mookiah, Muthu Rama Krishnan; Subburaj, Karupppasamy; Burian, Egon; Sollmann, Nico; Kirschke, Jan S.; Karampinos, Dimitrios C.; Baum, Thomas (Frontiers in Endocrinology, 2020)
Objective: Vertebral bone marrow composition has been extensively studied in the past and shown potential as imaging biomarker for osteoporosis, hematopoietic and metabolic disorders. However, beyond quantitative assessment of bone marrow fat, little is known about its heterogeneity. Therefore, we investigated bone marrow heterogeneity of the lumbar spine using texture analysis of chemical-shift-encoding (CSE-MRI) based proton density fat fraction (PDFF) maps and its association with age, sex and anatomical location. Methods: 156 healthy subjects were scanned (age range: 20–29 years, 12/30 males/females; 30–39, 15/9; 40–49, 5/13; 50–59, 9/27; ≥60: 9/27). A sagittal 8-echo 3D spoiled-gradient-echo sequence at 3T was used for CSE-MRI-based water-fat separation at the lumbar spine. Manual segmentation of vertebral bodies L1-4 was performed. Mean PDFF and texture features (global: variance, skewness, kurtosis; second-order: energy, entropy, contrast, homogeneity, correlation, sum-average, variance, dissimilarity) were extracted at each vertebral level and compared between age groups, sex, and anatomical location. Results: Mean PDFF significantly increased from L1 to L4 (35.89 ± 11.66 % to 39.52 ± 11.18 %, p = 0.017) and with age (females: 27.19 ± 6.01 % to 49.34 ± 7.75 %, p < 0.001; males: 31.97 ± 7.96 % to 41.83 ± 7.03 %, p = 0.025), but showed no difference between females and males after adjustment for age and BMI (37.13 ± 11.63 % vs. 37.17 ± 8.67 %; p = 0.199). Bone marrow heterogeneity assessed by texture analysis, in contrast to PDFF, was significantly higher in females compared to males after adjustment for age and BMI (namely contrast and dissimilarity; p < 0.031), demonstrated age-dependent differences, in particular in females (p < 0.05), but showed no statistically significant dependence on vertebral location. Conclusions: Vertebral bone marrow heterogeneity, assessed by texture analysis of PDFF maps, is primarily dependent on sex and age but not on anatomical location. Future studies are needed to investigate bone marrow heterogeneity with regard to aging and disease.